Incubation with a Complex Orange Essential Oil Leads to Evolved Mutants with Increased Resistance and Tolerance - Daniel Berdejo; Elisa Pagán; Natalia Merino; Rafael Pagán; Diego García-Gonzalo (MDPI AG, 2020)
Emergence of strains with increased resistance/tolerance to natural antimicrobials was evidenced after cyclic exposure to carvacrol, citral, and (+)-limonene oxide. However, no previous studies have reported the development of resistance and tolerance to complex essential oils (EOs). This study seeks to evaluate the occurrence of Staphylococcus aureus strains resistant and tolerant to a complex orange essential oil (OEO) after prolonged cyclic treatments at low concentrations. Phenotypic characterization of evolved strains revealed an increase of minimum inhibitory and bactericidal concentration for OEO, a better growth fitness in presence of OEO, and an enhanced survival to lethal treatments, compared to wild-type strain. However, no significant differences (p > 0.05) in cross-resistance to antibiotics were observed. Mutations in hepT and accA in evolved strains highlight the important role of oxidative stress in the cell response to OEO, as well as the relevance of the cell membrane in the cell response to these natural antimicrobials. This study demonstrates the emergence of S. aureus strains that are resistant and tolerant to EO (Citrus sinensis). This phenomenon should be taken into account to assure the efficacy of natural antimicrobials in the design of food preservation strategies, in cleaning and disinfection protocols, and in clinical applications against resistant bacteria.